Telemedicine in Arab Countries: Innovation, Research Trends, and Way Forward - Waqas, Ahmed; Mehmood, Shariq; Jawwad, Arwah Muhammad; Pittam, Bradley; Kundu, Shantanu; Correia, Jorge César; AlMughamis, Nouf (Frontiers in Digital Health, 2021)
Background The progress and innovation in telemedicine within the middle eastern countries has not been heavily monitored. Therefore, the present study aims to analyze the scholarly work conducted in the Arab world, using reproducible statistical and scientometric techniques. Methods An electronic search of Web of Science (WoS, core database) had been conducted through use of an extensive search strategy comprising of keywords specific to the Arab region, EMRO countries, telehealth, medical conditions and disorders. A total yield of 1630 search results were processed, indexed through July 7, 2020. CiteSpace (5.7.R1, Drexel University, Pennsylvania, USA) is a Java-based application; a user-friendly tool for conducting scientometric analyses. Results The present analyses found a lack of innovation in the field of digital health in the Arab countries. Many gaps in research were found in Arab countries which will be discussed subsequently. Digital health research was clustered around themes of big data and artificial intelligence, a lack of progress was seen in telemedicine and digital health. Furthermore, only a small proportion of these publications had principle or corresponding authors from Arab countries. A clear disparity in digital health research in the Arab world was evident after comparing these insights with our previous investigation on telemedicine research in the global context. Conclusion Telemedicine research is still in its infancy in the middle eastern countries. Recommendations include diversification of the research landscape and interdisciplinary collaborations in this area.